PENGARUH KEPEMILIKAN MANJERIAL, PROFITABILITAS, UKURAN PERUSAHAAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Property dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2012-2015) - Denny Nor Rohman, 13.05.52.0175; Suwarti, Titiek (Students Journal of Accounting and Banking, 2017)
This researchs purpose is to examine and to analyze the influence of Managerial Ownership, Profitability with proxy (Return On Assets), firm size, and Corporate Social Responsibility (CSR) on Corporate Value with proxy (Price Book Value) toward property and real estate companies which registered in Bursa Efek Indonesia (BEI). This researchs population is property and real estate companies which registered at Bursa Efek Indonesia (BEI) that has reported their annual report and financial report completely in between 2012-2015. This researchs sample which including in the criteria was 212 companies using purposive sampling. The analysis method in this research used double linear regression analysis. This researchs result found that the variable of Managerial Ownership and firm size were significant negative toward the corporate value, the variable of Profitability was significant postive toward the corporate value, and the variable of Corporate Social Responsibility (CSR) was non significant negative toward the corporate value.Keywords: Managerial Ownership, Profitability (ROA), Firm Size, Corporate Social Responsibility (CSR), Corporate Value (PBV)